The Comparison of Conflict Solving and Quality of Life of Opium and Stimulants Addicts - Tayebe Ameli; Khadijeh Abolmaali; Beheshteh Mirzaei (Drug Control Headquarters, Research and Education Office, 2013)
Aim: The aim of present research was to compare of conflict solving and quality of life of opium and stimulant addicts. Method: For this purpose, 74 opium addicts and 74 stimulant addicts selected of 3 clinics in 6 and 11 regions by clustering random sampling. Conflict solving questionnaire and quality of life administered among selected samples. Results: The results showed that there was significant difference between the mean scores of opium and stimulant addicts on conflict solving and quality of life. That is except of positivism on all subscales of conflict solving (namely: space and position, understanding clearness, attention to needs versus desires, mutually power distribution, primary focus to future, and focus on learning of past, completion of practical steps, cautious consideration) there were significant differences between two groups. Also, on all subscales of quality of life (namely: physical functioning, physical limitation, affective limitation, energy and frisk, affective health, social performance, and general health) except of pain there were significant differences between two studied groups. Conclusion: It seemed that people who were addicted to opium used more appropriate methods on conflict solving in comparison to stimulants addicts also, they have better quality of life.